PENGARUH KARAKTERISTIK CEO TERHADAP MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Edi, Edi; Cristi, Cristi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aimed to examine the effect of CEO characteristics on earnings management. The research sample consisted of 510 listed on the IDX-IC sectoral index of the Indonesia Stock Exchange during the year of observation (2016-2020). Sample selection was done by purposive sampling technique. The research data were tested as a whole using the panel regression method. The results showed that CEO gender, CEO turnover, CEO expertise and CEO citizenship were not directly significant in influencing earnings management, and CEO age and CEO tenure had a significant positive effect on earnings management.